Structural and optical properties of AlN/GaN and AlN/AlGaN/GaN thin films on silicon substrate prepared by plasma assisted molecular beam epitaxy (MBE) - Ho Xin Jing; Che Azurahanim Che Abdullah; Mohd Zaki Mohd Yusoff; Azzafeerah Mahyuddin; Zainuriah Hassan (Results in Physics, 2019)
In this study, the Aluminium Nitride/Gallium Nitride (AlN/GaN) layers and Aluminium Nitride/Aluminium Gallium Nitride/Gallium Nitride (AlN/AlGaN/GaN) layer heterostructures were successfully created using technique known as plasma-assisted molecular beam epitaxy (MBE) on silicon substrate. Gallium (7 N) and Aluminium (6 N5) of high purity were used to grow GaN, AlN and AlGaN respectively. The structural and optical properties of the prepared AlN/GaN and AlN/AlGaN/GaN layer heterostructures were investigated by means of atomic force microscope (AFM), X-ray diffraction (XRD), photoluminescence spectroscopy (PL) and Raman spectroscopy. AFM measurement demonstrated that the root mean square of surface roughness for AlN/GaN and AlN/AlGaN/GaN heterostructures are 3.677 nm and 10.333 nm respectively. XRD data indicated that the samples have typical diffraction pattern of hexagonal structure. Raman spectra revealed all four Raman-active modes present inside both samples. PL spectra data showed the yellow luminescence which corresponds to the deep energy levels due to imperfections of AlN did not appear. Thus, PL observation indicated that the thin film of AlN/GaN and AlN/AlGaN/GaN layers have good optical quality and looks promising for various target applications in optoelectronics, photovoltaic and radiofrequency applications. Keywords: Aluminium Nitride, Aluminium Gallium Nitride, Gallium Nitride, Thin film, MBE, Silicon